1992
DOI: 10.1126/science.257.5071.784
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of Atmospheric Mercury Deposition in Midcontinental North America

Abstract: Mercury contamination of remote lakes has been attributed to increasing deposition of atmospheric mercury, yet historic deposition rates and inputs from terrestrial sources are essentially unknown. Sediments of seven headwater lakes in Minnesota and Wisconsin were used to reconstruct regional modern and preindustrial deposition rates of mercury. Whole-basin mercury fluxes, determined from lake-wide arrays of dated cores, indicate that the annual deposition of atmospheric mercury has increased from 3.7 to 12.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
316
5
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(344 citation statements)
references
References 38 publications
21
316
5
2
Order By: Relevance
“…However, in those cases where mercury yields from asphalt shingle roofs exceeded those from metal roofs, the difference was much greater (3-8 times greater) than when the yields from metal roofs exceeded those from asphalt shingle (1-2 times greater). Regional atmospheric fallout is generally thought to be the major source of mercury in the environment (Swain et al, 1992) but does not explain the elevated concentrations of mercury often seen in urban sediments, thus the possibility that asphalt shingle roofs may be a source of mercury to the urban environment is intriguing and warrants further investigation.…”
Section: Nd International Symposium On Contaminated Sediments Physicamentioning
confidence: 99%
“…However, in those cases where mercury yields from asphalt shingle roofs exceeded those from metal roofs, the difference was much greater (3-8 times greater) than when the yields from metal roofs exceeded those from asphalt shingle (1-2 times greater). Regional atmospheric fallout is generally thought to be the major source of mercury in the environment (Swain et al, 1992) but does not explain the elevated concentrations of mercury often seen in urban sediments, thus the possibility that asphalt shingle roofs may be a source of mercury to the urban environment is intriguing and warrants further investigation.…”
Section: Nd International Symposium On Contaminated Sediments Physicamentioning
confidence: 99%
“…For example, inputs of mercury (Hg) to a waterbody can be influenced by atmospheric deposition (2), geology (3), soil and vegetation type (4), and large precipitation events (5). Increases in water temperature, dissolved organic carbon (DOC), and sulfate (SO 4 2Ϫ ) and declines in pH can increase in-lake Hg methylation (6).…”
mentioning
confidence: 99%
“…Atmospheric Hg is then deposited to surface soil, water bodies, and plants by dry and wet processes, where it imposes toxicity to organisms. It is reported that the present annual deposition rate of atmospheric Hg is approximately 3.4 times of preindustrial rate (Swain et al 1992), and the recent average Hg accumulation rate in sediment is 4.9 times higher than that in the 1900s (Rood et al 1995). As the largest anthropogenic Hg emission country over the world, China has received considerable concerns regarding the issue of Hg.…”
Section: Introductionmentioning
confidence: 99%